Refugium : an exploration through landscapes of liminality - Kaplan, Luke (Rhodes University, Faculty of Humanities, Department of Fine Art, 2014)
Loosely following a narrative form and structure, this thesis begins, in chapter one, by considering people who occupy a peripheral position in - or on the fringe of - society. In so doing, it analyses the dichotomy created between centre and periphery, the line between qualities or features that are set up as different or opposed. The chapter begins by contextualising my own engagement with the themes and narratives dealt with. It then looks at the representation and significance of historical and cultural characters such as the tramp and the wanderer, the medieval wildman and the outcast, the madman and the prophet, and relates this to some extent to my own narrative. The dichotomy between culture and nature is thus examined here. The paper then moves on, in chapter two, to examine concerns around landscape, and considers how we engage or separate ourselves from it. The theme of walking is examined closely from an experiential, phenomenological standpoint, especially as an activity which allows greater connection to, and engagement with, the landscape. The relationship between landscape, place, and identity is also explored, looking at how identity is interwoven with connection to place, and, broadly, what this might mean for displaced people. These discussions and ideas are then brought to bear again on my personal narrative. In chapter three I explore again the separation between dichotomous concepts as looked at in chapter one; I examine the separations between, and within, people, as well as between people and their environment. Here, however, the line of separation is explored not as an impermeable barrier, but as a liminal space of potential and possibility. With this in mind I look at sacred or liminal places within the landscape, as well as the idea of the sublime. I also consider the camera from this perspective, and finally present my own exhibition and body of work, reviewing it in the light of the narratives and themes explored through the thesis.
Keywords: Landscapes in art; Memory in art; Exile (Punishment) in art; Marginality, Social, in art; Art and photography